The Animal Rights Struggle : An Essay in Historical Sociology - Traïni, Christophe (Protest and social movements ;, 2019)
Since the early nineteenth century, numerous campaigns have denounced the mistreatment of animals. This book compares the British and French histories of the animal-protection movement to retrace its origins and impact up to the present day. As Christophe Traïni shows, the struggle for animal rights - inextricably linked to the rise of philanthropy and established long before the birth of the ecology movement - developed out of several important social and political processes, including changes in sensibilities and socially approved emotions, new definitions of what constitutes legitimate violence, and the influence of religious beliefs.